Socio-Cognitive Factors Associated With Condom Use, Multiple Sexual Partnerships, and Contraception Use Among Sexually-Active Adolescent Girls in Uganda - Nalukwago, Judith; Crutzen, Rik; Borne, Bart van den; Bukuluki, Paul M.; Bufumbo, Leonard; Burke, Holly M.; Field, Samuel; Zikusooka, Amos; Fiedler, Anne A.; Alaii, Jane (Global Journal of Health Science, 2018)
Many adolescent girls start sexual activity early which exposes them to health risks of HIV and unplanned pregnancies. However, adolescent girls are less likely than boys to initiate discussion or demand use of condoms. Multiple sexual partnerships among girls are reported to be on the rise with eminent transactional sex and pre-marital relationships. The unmet need for contraception among adolescent girls is also high. A cross-sectional survey covering 16 districts in Uganda assessed the socio-cognitive factors associated with condom use, multiple sexual partnerships and contraception use among sexually active adolescent girls (N=255). There were strong associations between feeling confident to discuss contraceptive methods with a partner (OR = 9.41, 95 % CI = 3.54, 25.06), being comfortable to use contraception (OR = 30.61, 95% CI = 4.10, 228.64), discussing contraception use with someone (OR = 10.53, 95% CI = 5.61, 19.78), and contraception use. Whereas knowledge was found to have no significant relationship with service uptake, information services remain important in clearing any misconceptions and addressing any health concerns. It is imperative to explore communication factors including skills development and providing adequate health information to guide dialogue among adolescents and their key influencers.
Keywords: Adolescent girls; Condom use; Contraception use; Multiple sexual partnerships